2021
DOI: 10.1080/01972243.2020.1870597
|View full text |Cite
|
Sign up to set email alerts
|

Return of the regulatory state: A stakeholder analysis of Australia’s Digital Platforms Inquiry and online news policy

Abstract: In this paper, we undertake a stakeholder analysis of the Australian Competition and Consumer Commission's Digital Platforms Inquiry to understand the nature and influence of different forms of public input. Our findings show that nation-state regulation of digital platforms is now very much on the policy agenda worldwide, with a focus upon the competition policy dimensions of platform regulation. The second key finding is that the regulatory activism of the ACCC have ensured that the Inquiry and its findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 22 publications
0
12
0
7
Order By: Relevance
“…Depending on whether it has a feature of democracies or autocratic states, the form of national interventions in content removal may vary, as reflected in factors such as the type of requester, the primary reason for the request, pattern, and intensity of requests over time. Although it has been argued that a long history of Internet control applies to most countries regardless of the characteristics of the political system (Flew, 2021), it remains to be answered "how" these controls were exercised and patterned by different types of political regimes, especially in the realm of content moderation.…”
Section: Content Analysis Definition and Measuresmentioning
confidence: 99%
See 2 more Smart Citations
“…Depending on whether it has a feature of democracies or autocratic states, the form of national interventions in content removal may vary, as reflected in factors such as the type of requester, the primary reason for the request, pattern, and intensity of requests over time. Although it has been argued that a long history of Internet control applies to most countries regardless of the characteristics of the political system (Flew, 2021), it remains to be answered "how" these controls were exercised and patterned by different types of political regimes, especially in the realm of content moderation.…”
Section: Content Analysis Definition and Measuresmentioning
confidence: 99%
“…Based on continued criticism over limited regulatory oversight, the focus of the discussion has shifted from whether or not to regulate, to who should be in charge of regulating harmful online content and what form of accountability and transparency should be required of digital platforms in relation to content‐moderation decisions. Flew, Gillett, et al (2021) found that the global regulatory environment is increasingly turning towards greater external regulation.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In this jurisdiction, the major outcome of this recent international reform moment has been an inquiry around digital platforms, which Chapters 6, 7 and 9 in this volume discuss in more detail. The first major proposal to emerge from the inquiry was the News Media Bargaining Code (NMBC), which forced platforms to form commercial agreements with news outlets around the use of their content (Flew, Gillett, Martin and Sunman 2021). However, somewhat hidden in the Act that featured this headline reform were a number of additional standards that designated platforms would be required to follow.…”
Section: Algorithmic Governance: Transparency Diversity or Departurementioning
confidence: 99%
“…Many of these reform agendas also appear to align with the goals of the commercial media industry or interest groups across the cultural policy sector. This speaks to a wider historical problem across media policymaking, which sees powerful actors prioritized over civil society and the wider public (Flew, Gillett, Martin, and Sunman 2021;Freedman 2008).…”
Section: Major Concepts In News Algorithms and The Public Interestmentioning
confidence: 99%